(untitled) (Global Journals of Research in Engineering, 2012)
Propeller cavitation is a major problem in ship operation and the costs of repair and maintenance is high for ship-owners. Proper design of propeller plays a very important role in life cycle and the performance of a vessel. The use of simulation to observe various parameters that affect cavitations can be helpful to optimize propeller performance. This project designs and simulates cavitations flow of a Kaplan series, Fixed Pitch Propeller (FPP) of a 48-metres Multipurpose Deck Ship at 11 knots. Simulation test was carried out for laminar and turbulent flow using Computational Fluid Dynamics (CFD) approach to observe cavitations occurrence at selected radius. The parameters considered are pitch angle, angle of attack, viscosity of sea water, operating vapour pressure in the sea water, engine power, lift and drag vectors of each of the blade sections, and resultant velocity of the fluid flow. Comparison of performance is made and it compares well with the theory. Thrust coefficient (KT), torque coefficient (KQ), thrust (T), advance coefficient (J), and cavitations number (#x3C3;), were calculated to deduce efficiency and validate the model. The study can be used to build a prototype physical model that could be beneficial for future additional experimentation investigation.